2016
DOI: 10.1080/15374416.2015.1110822
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Commitment Therapy versus Cognitive Behavior Therapy for Children With Anxiety: Outcomes of a Randomized Controlled Trial

Abstract: Acceptance and Commitment Therapy (ACT) has a growing empirical base in the treatment of anxiety among adults and children with other concerns. This study reports on the main outcomes of a randomized controlled trial of ACT and traditional cognitive behavioral therapy (CBT) in children with a Diagnostic and Statistical Manual of Mental Disorders (4th ed.) anxiety disorder. Participants were 193 children from urban Sydney, Australia, who were block-randomized to a 10-week group-based program of ACT or CBT or a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 59 publications
7
48
0
3
Order By: Relevance
“…AFQ-Y findings were in line with those emerging up to 3MFU, as previously reported [14], with both ACT and CBT having similarly positive outcomes. This supports the possibility that defusion and restructuring strategies are simply different tools that can be used to change behavior when problematic thoughts and feelings arise, rather than one being superior to the other.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…AFQ-Y findings were in line with those emerging up to 3MFU, as previously reported [14], with both ACT and CBT having similarly positive outcomes. This supports the possibility that defusion and restructuring strategies are simply different tools that can be used to change behavior when problematic thoughts and feelings arise, rather than one being superior to the other.…”
Section: Discussionsupporting
confidence: 76%
“…Two randomized clinical trials of over 100 adults with anxiety found both ACT and CBT to be highly effective over time, with similar outcomes [12,13]. Hancock, et al [14] reported similar results in children and adolescents up to 3 months post-treatment.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations